Research on Aerothermoelasticity for Hypersonic Inlet with Complex Internal Flow - Kun YE; Yi-fan ZHANG; Zheng-yin YE (气体物理, 2023)
Hypersonic inlet is very easy to induce aerothermoelastic problems under the aerodynamic load and aero-thermal action of complex flow. Deeply understanding the aerothermoelasticity mechanism of complex internal flow is of great significance for the detailed design of hypersonic inlet in the future. In this paper, a static/dynamic aerothermoelastic analysis framework was established, and the mechanism of the influence of static/dynamic aerothermoelasticity on the flow field structure and performance of three-dimensional hypersonic inlet was studied in depth. The results of static aerothermoelastic analysis show that the aerothermoelastic deformation obtained by the two-way coupling method is relatively large, and the deformation of the leading edge of the inlet lip is the largest. The structural deformation changes the shock wave structure near the lip edge, enhances the shock wave intensity inside the inlet, increases the length of the separation zone and the temperature of the outer wall, and changes the flow field at the outlet. At the same time, the aerothermoelastic deformation will lead to the increase of mass flow coefficient and pressure rise ratio, and reduce the total pressure recovery coefficient. The results of dynamic aerothermoelastic analysis show that the displacement response of the structure converges when the aerodynamic heating is not taken into account. After considering aerodynamic heating, the structural displacement response presents a limit cycle trend. Aerodynamic heating may change the dynamic response characteristics of the inlet structure. Because the structural frequencies of the intake ports are very close to each other, ″beat″ phenomenon exists in the dynamic response of the structure. The leading edge deformation is large and the amplitude is small, while the trailing edge deformation is small and the amplitude is large. The structure vibration leads to significant dynamic changes in the flow field structure and significant fluctuations in the performance parameters, especially for the pressure rise ratio at the outlet. It is hoped that the research in this paper will deepen the understanding of the aerothermoelasticity in the complex flow structure of the inlet, in order to provide reference for the detailed design of the inlet in the future.